The effectiveness of digital health versus standard care on exclusive breastfeeding duration among postpartum mothers in LMIC: Systematic review and meta-analysis - Thiwawan Thepha; Gillian Carr; Debbi Marais; Jatuporn Kuasri; Kritsana Klangphaow; Juraporn Tangpukdee (Digital Health)
Objective This study aims to evaluate the effectiveness of digital health interventions compared to standard care in promoting exclusive breastfeeding (EBF) among postpartum women in low-and middle-income countries (LMICs). Methods The PRISMA guidelines of reporting were followed for the searching of four databases and screening following eligibility criteria: articles presenting digital health interventions, conducted as randomized control trials (RCTs), quasi-experimental, or mixed-method studies, reporting on EBF duration and early initiation of breastfeeding, and published in the English language were included. Results Of 1595 articles screened, only 10 published between 2013 and 2023 met the criteria. Most studies were from Nigeria (n = 3), with others from Kenya, South Africa, Ethiopia, China, India, and Lebanon. Six were RCTs, and four were quasi-experimental. The meta-analysis shows digital health interventions significantly increase EBF duration, with the strongest effects at 6 months (odds ratio (OR) = 2,1.66–2.40), followed by 5, 3, 2, and 1 month postpartum, including the initial feed. Conclusion This suggests digital health interventions have the potential to enhance breastfeeding practices among postpartum mothers in LMICs. For future research, it is essential to consider accessibility, delivery intervention, healthcare professional collaboration, and the sustainable development of digital health interventions for postpartum mothers in LMICs.